Analysis the size of construction of fishing vessels 15 GT in tradisional shipyard Sawang Ba'u, South Aceh Regency against the Indonesian Classification Bureau Rules. - Raju Shaumi Aljika (Jurnal Kelautan dan Perikanan Indonesia, 2023)
Fishing vessels are one of the fishing units that play a very important role for fishermen, both as a means of transportation from fishing areas to fishing areas and vice versa. The construction of fishing boats is very diverse, starting from the traditional nature based only on hereditary knowledge to the modern characteristics that have used technological advances. The Indonesian Classification Bureau (BKI) is an organization that sets technical standards for conducting design, construction and marine survey activities related to floating facilities, including ships and offshore ship construction. The purpose of this study was to obtain measuring data for the construction parts of a 15 GT purse seine fishing vessel and to find out the suitability of the construction size of a 15 GT purse seine fishing vessel in the traditional shipyard of South Aceh Regency with the rules of the Indonesian Classification Bureau. The research will be carried out in September 2022 at the Sawang Ba'u traditional shipyard, South Aceh District. The types of data collected in this study were primary data and secondary data using interview and observation methods to direct measurements which were then analyzed using an analysis scantling number. The results showed that on average the size of the suitability of the construction of fishing boats found in the Sawang Ba'u shipyard met the BKI criteria or was the same as the suitability measure that had been determined by the BKI book. However, there are several constructions that are not suitable, such as the thickness of the outer shell is smaller (width 230 mm), smaller ship rafters (width 40 mm), smaller kim shipbuilding (width 30 mm), and the machine foundation is smaller (width 30 mm and the height 135 mm) from BKI provisions.